Flexible Solar Cells: Impact of Na Doping on the Carrier Transport Path in Polycrystalline Flexible Cu2ZnSn(S, Se)4 Solar Cells (Adv. Sci. 21/2020). Issue 21 (4th November 2020) - Jeong, Woo‐Lim; Kim, Kyung‐Pil; Kim, Juran; Park, Ha Kyung; Min, Jung‐Hong; Lee, Je‐Sung; Mun, Seung‐Hyun; Kim, Sung‐Tae; Jang, Jae‐Hyung; Jo, William; Lee, Dong‐Seon
Abstract : In article number 1903085, Woo‐Lim Jeong, Kyung‐Pil Kim, Dong‐Seon Lee, and co‐workers analyze the effects of Na doping on polycrystalline flexible CZTSSe solar cells. When doping is excessive, a device shows low contact potential difference and fill factor and selects a worse carrier transport path even though the built‐in potential becomes stronger. On the other hand, the optimized CZTSSe solar cell clearly showed the enhancing effect of Na doping.